Melatonin mitigates cadmium phytotoxicity through modulation of phytochelatins biosynthesis, vacuolar sequestration, and antioxidant potential in Solanum lycopersicum L - Hasan, Md. Kamrul; Ahammed, Golam Jalal; Yin, Lingling; Shi, Kai; Xia, Xiaojian; Zhou, Yanhong; Yu, Jingquan; Zhou, Jie (Frontiers in Plant Science, 2015)
Melatonin is a ubiquitous signal molecule, playing crucial roles in plant growth and stress tolerance. Recently, toxic metal cadmium (Cd) has been reported to regulate melatonin content in rice; however, the function of melatonin under Cd stress, particularly in higher plants, still remains elusive. Here, we show that optimal dose of melatonin could effectively ameliorate Cd-induced phytotoxicity in tomato. The contents of Cd and melatonin were gradually increased over time under Cd stress. However, such increase in endogenous melatonin was incapable to reverse detrimental effects of Cd. Meanwhile, supplementation with melatonin conferred Cd tolerance as evident by plant biomass and photosynthesis. In addition to notable increase in antioxidant enzymes activity, melatonin-induced Cd stress mitigation was closely associated with enhanced H+-ATPase activity and the contents of glutathione and phytochelatins. Although exogenous melatonin had no effect on root Cd content, it significantly reduced leaf Cd content, indicating its role in Cd transport. Analysis of Cd in different subcellular compartments revealed that melatonin increased cell wall and vacuolar fractions of Cd. Our results suggest that melatonin-induced enhancements in antioxidant potential, phytochelatins biosynthesis and subsequent Cd sequestration might play a critical role in plant tolerance to Cd. Such a mechanism may have potential implication in safe food production.